Structure of Matrices and Their Divisors over the Domain of Principal Ideals - Prokip, V. M.; Прокіп, В. М. (Institute of Mathematics, NAS of Ukraine, 2002)
We investigate the structure of matrices and their divisors over the domain of principal ideals.